Effect of Lactobacillus rhamnosus on the response of Galleria mellonella against Staphylococcus aureus and Escherichia coli infections - Jorjão, Adeline Lacerda [UNESP]; de Oliveira, Felipe Eduardo [UNESP]; Leão, Mariella Vieira Pereira; Jorge, Antonio Olavo Cardoso [UNESP]; de Oliveira, Luciane Dias [UNESP] (Springer Nature, 2018)
This study evaluated the prophylactic effects of the live or heat-killed probiotic strain Lactobacillus rhamnosus ATCC 7469 in Galleria mellonella, inoculated with Staphylococcusaureus or Escherichia coli. L. rhamnosus suspension was prepared and a part of it was autoclaved to obtain heat-killed lactobacilli. The larvae were inoculated of these suspensions and pathogenic. The survival of the larvae was observed during 7 days and after 24 h of inoculation haemocytes counted, melanization and nitric oxide production were analyzed. Larvae survival rate increased in the group inoculated with heat-killed L. rhamnosus, however, with no statistical difference. There was a significant increase in total haemocyte counts in all test groups. Haemolymph melanization and nitric oxide production were higher in the group inoculated with L. rhamnosus and infected with S. aureus. It was concluded that, in this model of infection, heat-killed L. rhamnosus ATCC 7469 promoted greater protection in Galleria mellonella infected with S. aureus or E. coli.
Keywords: Curve survival; Galleria mellonella; Infection; Lactobacillus rhamnosus; Melanization